Microalgae Harvesting via Flocculation: Impact of PH, Algae Species and Biomass Concentration. Issue 1 (9th May 2018) - Maji, Gopal Krishna; Choudhury, Sayantan; Hamid, Shoaib; R, Prashanth; Arjunan, Selvam; G, Sibi
No abstract available